Challenges and future of HER2-positive gastric cancer therapy - Ma, Chenzhe; Wang, Xiao; Guo, Jiwu; Yang, Bo; Li, Yumin (Frontiers in Oncology, 2023)
Gastric cancer is the fifth most common cancer worldwide, and the treatment of advanced gastric cancer has relatively little progress. With the continuous development of molecularly targeted therapy for tumors, it has been discovered that human epidermal growth factor receptor 2 (HER2) contributes to the poor prognosis and pathogenesis of various cancers. In order to treat HER2-positive advanced gastric cancer, Trastuzumab has emerged as the first first-line targeted medication used in conjunction with chemotherapy. The consequent Trastuzumab resistance has become an important issue, and various new HER2-targeted gastric cancer drugs are emerging to address this challenge. This review’s primary concern is the drug mechanism of various HER2-positive gastric cancer targeted therapy and fresh techniques of detection.